Determination of Biochemical Content and Antioxidant Activity of Calliergonella cuspidata (Hedw.) Loeske - Turu, Dilay; Bozkurt, Selime Deniz; Yaman, Cenker; Gül, Gizem; Benek, Atakan; Canlı, Kerem (Anatolian Bryology, 2024)
Since ancient times, humans have been utilizing various plants for medicinal purposes, a practice that has persisted from early civilizations to the present day. Plants serve as rich sources of biomolecules, although many of their contents remain unidentified. Bryophytes are considered important reservoirs for new natural products, with mosses being less explored compared to liverworts despite their broader species diversity. This study contains the content analysis of ethanol, methanol, and n-hexane extracts of Calliergonella cuspidata to predict and compare their biochemical compound profiles. The ethanol extract revealed the presence of 3-Formyl-N-methyl-9-[phenylethynyl]dibenzo2,3-a:5,6-a'-thiazine and Eicosane, while Beta-Elemene and Neophytadiene were identified in the methanol extract, and predominantly alkanes were found in the n-hexane extract. Subsequently, antioxidant activity was determined using the DPPH method with the ethanol extract, yielding an EC50 value of 1.0237 mg/ml.
Keywords: Bitki Bilimi (Diğer); Botany (Other); Bryophytes; Moss; Calliergonella cuspidata; GC/MS; Antioxidant; Türkiye; Briyofitler; Karayosunları; Calliergonella cuspidata; GC/MS; Antioksidan; Türkiye; 3. Good health